The Effects of FOMO on Investment Behavior in the Stock Market - Idris, Hariany (Manunggal Halim Jaya, 2024)
This study explores the impact of Fear of Missing Out (FOMO) on stock market investment behavior, focusing on how psychological and emotional factors influence investors' decision-making processes. The primary objective of the research is to investigate the relationship between FOMO and key behavioral trends, such as overtrading, speculative investing, and the formation of asset bubbles. A qualitative research approach was employed, utilizing a literature review of existing studies on behavioral finance, FOMO, and stock market dynamics. The findings indicate that FOMO significantly affects investors by amplifying emotional reactions to market trends, leading to irrational decisions that prioritize short-term gains over long-term financial stability. Social media and technology play a critical role in amplifying FOMO, creating herd behavior that contributes to market volatility and speculative bubbles, as seen in phenomena like